Growth and coalescence studies of (112‾2) oriented GaN on pre‐structured sapphire substrates using marker layers. Issue 1 (14th August 2015) - Caliebe, Marian; Han, Yisong; Hocker, Matthias; Meisch, Tobias; Humphreys, Colin; Thonke, Klaus; Scholz, Ferdinand
Abstract: In this article, the growth and coalescence of semi‐polar ( 11 2 ‾ 2 ) oriented GaN layers, deposited on pre‐structured r ‐plane sapphire substrates, is studied with the help of Si‐doped marker layers. It has been found to be very important to adjust the shape of the initial GaN stripes by varying the growth temperature to obtain not only a smooth surface, but also a small density of basal plane stacking faults (BSFs) and threading dislocations (TDs) on the wafer surface. With the help of transmission electron microscopy (TEM) and cathodoluminescence measurements (CL), we can conclude that during growth, we need to achieve a compromise between small BSF density, small TD density, and perfect coalescence with smooth surface, free of fissures, and other growth artifacts. Also the formation of arrow‐head‐shaped surface artifacts called "chevrons"1 2 can be understood to be caused by imperfect coalescence. We observe with the help of the marker layers that the growth rate fluctuates between neighboring stripes. This effect strongly increases for higher growth temperature.